Discriminant Analysis of Students' Spatial Ability in Understanding Flat-Sided Geometric Shapes - Lutfi, Muh. Khaedir; Herman, Tatang; Mulyaning A, Endang Cahya (International Journal of Pedagogy and Teacher Education, 2025)
Spatial ability is a crucial aspect that supports students in visualizing and understanding abstract mathematical concepts, particularly flat-sided geometric shapes in geometry learning. This study aims to identify the factors that differentiate students with low and high spatial abilities through discriminant analysis. The factors analyzed include Mental Rotation, Spatial Orientation, Visualization, Spatial Relation, and Spatial Perception, measured using a spatial ability test. The test instrument consisted of five questions developed based on the spatial ability framework offered by Maier and validated by mathematics and learning evaluation experts. A total of 34 ninth-grade students from a junior high school in Tangerang Regency were selected through purposive sampling. The analysis results showed that Visualization, Spatial Relation, and Spatial Perception were the main predictors that significantly differentiated the two groups. Visualization supports the ability to imagine geometric objects, Spatial Relation facilitates the understanding of relationships between objects, and Spatial Perception aids in recognizing the position and relationship of geometric elements. The resulting discriminant model had an eigenvalue of 13.967, indicating a strong discriminant power in separating student groups. Understanding these differentiating factors provides a foundation for designing effective learning strategies, such as the use of augmented reality (AR) applications and 3D modeling tools to enhance students’ comprehension of spatial figures. Furthermore, interventions using physical or virtual manipulatives can be tailored to students’ needs, assisting them in mastering the concept of flat-sided geometric shapes.